The nonlinear theory of the electron and ion beames interaction in a supercritical mode - Balakirev, V.A.; Onishchenko, N.I. (Вопросы атомной науки и техники, 2002)
The problem of REB and ion beam interaction at currents above space charge limiting values has been mathematically formulated. The method of Lagrangian variables has been used for the description of selfconsistent nonlinear dynamics of electrons and ions in collective fields of the beams. The simulation has been performed for the parameters of the experimental installation.